Evaluation on the Effectiveness of DOLE-OWWA Enterprise Development and Loan Program (EDLP) among Overseas Filipino Workers in the Selected Barangays of Tacurong City - Avendanio, Eddie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of the DOLE-OWWA Enterprise Development and Loan Program (EDLP) in promoting enterprise development among Overseas Filipino Workers (OFWs) in selected barangays of Tacurong City, Sultan Kudarat. Anchored on functionalist migration theory, neo-classical migration theory, and the New Economics of Labor Migration (NELM), the study examined how enterprise development and loan assistance contribute to entrepreneurial opportunities, business growth, and sustainable livelihoods among returning OFWs. A mixed-method research design was employed, combining qualitative and quantitative approaches. Data were gathered through in-depth interviews and survey questionnaires administered to thirteen informants from selected barangays and the Local Government Unit of Tacurong City using purposive sampling. Qualitative data were analyzed through textual analysis, while quantitative data were interpreted using descriptive ratings based on a five-point effectiveness scale. Findings revealed that the EDLP was highly effective in supporting eligible projects (grand mean = 4.69) and highly effective in providing working capital assistance (grand mean = 4.44). Beneficiaries reported successfully establishing and sustaining businesses that generated steady income and created employment opportunities within their communities. The study also identified education and training, as well as transportation and communication barriers, as factors affecting program implementation and beneficiary participation. Despite these challenges, respondents generally reported positive experiences and perceived the program as beneficial to their economic reintegration. The study concluded that the EDLP effectively supports entrepreneurship, enterprise development, and income generation among OFWs. It recommends strengthening and expanding the program, increasing access to loan opportunities, enhancing participation in training and information activities, and conducting further evaluations of program implementation. The study aligns with Sustainable Development Goal (SDG) 8 (Decent Work and Economic Growth), SDG 1 (No Poverty), SDG 9 (Industry, Innovation and Infrastructure), and SDG 17 (Partnerships for the Goals) by supporting entrepreneurship, income generation, enterprise development, and inter-agency collaboration for OFW reintegration. Its sustainability impact lies in promoting local economic development, employment creation, business sustainability, and evidence-based improvements in government reintegration and entrepreneurship support programs for returning migrant workers.
Keywords: Entrepreneurship; Enterprise Development and Loan Program (EDLP); Overseas Filipino Workers (OFWs); Reintegration; Sustainable Livelihoods; Tacurong City; Training and Education; Working Capital